A facile synthesis of 1-oxo-pyrrolo[2, 1-a]isoquinolines. Issue 9 (1st March 2017) - Voskressensky, Leonid G.; Borisova, Tatiana N.; Matveeva, Maria D.; Khrustalev, Viktor N.; Titov, Alexander A.; Aksenov, Alexander V.; Dyachenko, Svetlana V.; Varlamov, Alexey V.
Graphical abstract: Highlights: A novel approach towards polysubstituted pyrrolo[2, 1- a ]isoquinolines was developed. Migration of the aryl group accompanies the target molecule formation. Functional groups of the products can be used for further modification. Abstract: The facile synthesis of 1-oxo-pyrrolo[2, 1- a ]isoquinolines from the reaction of 1-aroyl-3, 4-dihydroisoquinolines and symmetrical alkynes in toluene is described. The novel compounds contain functional groups that are suitable for further modification.